Existence Results for Periodic Solutions of Nonautonomous Second-Order Differential Systems with $(q, p)$-Laplacian (Communications in Mathematical Research, 2021)
In this paper, we consider the existence for periodic solutions of nonautonomous second-order differential systems with $(q, p)$-Laplacian by using the leastaction principle and the minimax methods.
Keywords: periodic solution; $(q; p)$-Laplacian; critical point; saddle point theorem.